E-whanaungatanga : the role of social media in Māori political engagement - Waitoa, Joanne Helen (Massey University, 2013)
Social media are used increasingly worldwide to connect people and points of view. This thesis explores the role social media can play in enhancing Maori development via political engagement. It investigates the efficacy of using social media to increase Maori political awareness and participation using the Mana Party Facebook pages as a case study. It also examines the opportunities and implications of social media for indigenous development in general. Themes in the literature on social media and indigenous development include: identity politics; language revitalisation and cultural preservation; activism; knowledge management; networking and collaboration; and business and marketing. This qualitative study was informed by Kaupapa Maori and empowerment theories. It involves interviews with the Mana Party president, Mana Party Facebook page moderators, and users of the Mana Party Facebook pages. The interviews explored the objectives and outcomes of using social media to raise political awareness of Maori, finding that Mana Party objectives were met to varying degrees. It also found that social media has both positive and negative implications for indigenous development. Social media aligns with tikanga Maori through Tino Rangatiratanga and whanaungatanga. However, it can conflict with tikanga Maori due to lack of respect, cultural misappropriation, sharing sacred information, subversion of traditional hierarchy and absence of a ‘seen face’. There are thus tensions in the use of social media for political engagement among indigenous peoples. Finally, the thesis offers a framework of how to use social media with indigenous groups that emphasises the positive and mitigates the negative aspects of the platform.
Keywords: kāwanatanga; mana party; political participation; political parties

E-Whanaungatanga: The role of social media in Māori political empowerment - Waitoa, Joanne; Scheyvens, Regina; Warren, Te Rina (AlterNative: An International Journal of Indigenous Peoples, 2015)
Lower voter turnout and lack of political empowerment sees Māori engaging less than Pākehā (European New Zealanders) with the political system to the detriment of Māori development. This paper explores the potential of social media to enhance Māori development via political engagement. Mana Party Facebook pages are used as a case study to investigate if social media can encourage Māori political awareness and participation. Results found that social media has both positive and negative implications for political engagement and indigenous development. While social media aligns with tikanga Māori (values/customs) through tino rangatiratanga (self-determination) and whanaungatanga (relationships/networks), other aspects such as cultural misappropriation conflict with Māori values. The paper explores tensions in the use of social media for political engagement among indigenous peoples and offers a framework promoting e-whanaungatanga to illustrate how they might use social media in a way that emphasizes the positive and mitigates the negative aspects of the platform.